Hydraulic characterization of laterals as applied to selected radial collector wells at Belgrade groundwater source - Polomčić Dušan; Božović Đorđije; Bajić Dragoljub (Geološki Anali Balkanskoga Poluostrva, 2016)
The paper examines the possibility of hydraulic characterization of radial well laterals in a manner that does not require prior hydrodynamic analysis by simulating groundwater extraction conditions on a numerical model. The first step of the proposed approach is to assess the groundwater level regime formed in the capture zone when the well is operating, which is indicative of the functional condition of the laterals and the aquifer potential in terms of groundwater availability. Then the efficiency of the laterals is examined through the hydraulic function of the skin zone, depending on its filtration properties. An expression for groundwater flow from the aquifer to the laterals (commonly used to simulate laterals on a hydrodynamic model) is employed to define representative values of the conductance coefficient of the skin zone (as an indicator of colmation), and then applied to several wells at Belgrade Groundwater Source. The present research shows that a conductance coefficient of [Ks/ds]=1.0×10-4 s-1 can be considered as the threshold value in relation to which the effects of colmation of well laterals are exhibited, which is consistent with the results reported by researchers who studied the effect of skin zone conductance on the occurrence and nature of the so-called early drawdown at radial collector wells. In addition to gaining insight into the present condition of the laterals, the proposed approach can be used to study the progress of colmation at different points in time and to quantify the effectiveness of regeneration of laterals. [Projekat Ministarstva nauke Republike Srbije, br. OI176022, br. TR33039 i br. III43004]